2012
DOI: 10.1021/jf302848u
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Free Amino Acid, Protein, and Flavonoid Content in Jujube (Ziziphus jujube) Fruit during Eight Stages of Growth and Antioxidative and Cancer Cell Inhibitory Effects by Extracts

Abstract: Jujube (Ziziphus jujube) was analyzed at eight stages of ripeness (S1-8) for protein, by HPLC and mass spectroscopy for free amino acids and flavonoids, and by colorimetry for total flavonoids and antioxidative activity. The ripe fruit had lower levels of protein, flavonoids, and antioxidative activity than that of the unripe fruit. Free amino acids levels peaked at S5, due mainly to an increase in free asparagine. Extracts were also tested against four cell lines using the MTT cell viability assay. All growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
102
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 46 publications
11
102
1
1
Order By: Relevance
“…Choi et al and Wu et al demon-strated that the antioxidant capacity decreased with the maturity of fruits (Choi et al, 2012;Wu et al, 2012). In spite of this, the ABTSÁ -scavenging capacities found in this study were 2-3 times higher than the levels of other common fruits, such as apples, bananas, blackberries, cherries, grapes, kiwifruits, lemons, mangoes, peaches, pears, plums and watermelons (Fu et al, 2011).…”
Section: Antioxidant Capacitycontrasting
confidence: 74%
See 1 more Smart Citation
“…Choi et al and Wu et al demon-strated that the antioxidant capacity decreased with the maturity of fruits (Choi et al, 2012;Wu et al, 2012). In spite of this, the ABTSÁ -scavenging capacities found in this study were 2-3 times higher than the levels of other common fruits, such as apples, bananas, blackberries, cherries, grapes, kiwifruits, lemons, mangoes, peaches, pears, plums and watermelons (Fu et al, 2011).…”
Section: Antioxidant Capacitycontrasting
confidence: 74%
“…China has a large variety of jujube cultivars (over 700 selections) and accounts for 90% of the total jujube output worldwide, which makes China the largest producer of this common fruit (Zhao, Liu, & Tu, 2008). The Chinese jujube fruit has been used as a traditional Chinese medicine and admired for its favourable taste, high nutritional value and pharmaceutical benefits, such as anticancer, antiepileptic, anti-inflammatory, anti-insomnia, and neuroprotective effects, in cells, animals, and humans (Choi et al, 2012). Hence, jujube fruits can be consumed as a medicine homologous food.…”
Section: Introductionmentioning
confidence: 99%
“…26 Indeed, our data demonstrated that the content of glucose was higher in mature jujube than that of immature jujube, yet the sucrose amount was higher in immature jujube than that of the mature one. Choi et al (2012) revealed that mature jujube had a lower level of protein than that of the immature one, while mature jujube contained higher amounts of free amino acids than that of the immature one. 23 Our NMR results showed that the total amount of tested amino acids was higher in mature jujube than that of the immure one, which was in line with the studies by Choi et al (2012).…”
Section: ■ Discussionmentioning
confidence: 94%
“…23 Zozio et al (2014) proposed that, during ripening, the antioxidant activity may be more impacted by the flavonols and condensed tannins. 25 In contrast, other studies demonstrated that the antioxidative activity did not show significant correlation with the amount of flavonoids.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Flavones. 11 compounds were characterized as flavones, 10 of them were definitely identified via standard references comparisons except for compounds 30 (vicenin-2), which was tentatively deduced via comparing its molecular mass and MS/MS spectra with the literature data [28][29][30][31]. Majority of them exist in the form of glycosides with sugars attached to the flavonoid aglycones via C-O or C-C bond, except for 3 aglycones.…”
Section: Identification Of Flavonoidsmentioning
confidence: 99%